2022
DOI: 10.1002/mp.15675
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the ion collection efficiency of the Razor Nano Chamber for ultra‐high dose‐rate electron beams

Abstract: Background Ultra‐high dose‐rate (UHDR) irradiations (>40 Gy/s) have recently garnered interest in radiotherapy (RT) as they can trigger the so‐called “FLASH” effect, namely a higher tolerance of normal tissues in comparison with conventional dose rates when a sufficiently high dose is delivered to the tissue. To transfer this to clinical RT treatments, adapted methods and practical tools for online dosimetry need to be developed. Ionization chambers remain the gold standards in RT but the charge recombination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…films have been used in many previous FLASH experiments with doses higher than 10 Gy. 15,16,18 Although their doses were out of the optimal dose response range of EBT-3 films, the authors reported no issues in dosimetry. Nevertheless, only EBT-XD films were selected in our study to take advantage of the higher optimal dose response range (up to 40 Gy).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…films have been used in many previous FLASH experiments with doses higher than 10 Gy. 15,16,18 Although their doses were out of the optimal dose response range of EBT-3 films, the authors reported no issues in dosimetry. Nevertheless, only EBT-XD films were selected in our study to take advantage of the higher optimal dose response range (up to 40 Gy).…”
Section: Introductionmentioning
confidence: 96%
“…average 2 Gy/min), as reference dosimeters to quantify the ion collection efficiency of ion chambers at FLASH dose rate by assuming dose-rate independence in these films. 15,16 However, a recent study reported the average doserate dependence of response of EBT-3 and EBT-XD films when the dose was higher than 10 Gy 17 with an isochronous cyclotron-based proton FLASH. These findings motivated us to investigate dose-rate dependence of the response of films for a synchrotron-based proton FLASH beam, which was the second aim of the current study.…”
Section: Introductionmentioning
confidence: 99%
“…As the most promising beam-monitoring technique for electron FLASH LINACs is based on current transformers [43,44] which provides a direct current measurement at the LINAC exit window, the possibility of relating such measurement to dose is particularly interesting and may even represent a solution to the actual difficulties in dose monitoring. The interested reader could find details about the current FLASH dosimetric challenges in [43,45], together with some promising solutions: the FLASH diamond [46], FLASH ionization chambers [47-49], and using current technologies in the FLASH regimes [50,51]. This work presents and validates the determination of the absorbed dose to water in any clinical configurations by means of a purely Monte Carlo simulation, once the beam optics geometry is known and the beam current at the exit window is available.…”
Section: Discussionmentioning
confidence: 99%
“…Typical unfavourable characteristics for charge-based detectors are their dose rateand energy dependence and non-tissue equivalence. Several promising modifications to meet the demands of the UHDR beam dosimetry have however recently been investigated for ion chambers and diamond detectors [23][24][25][26]. For instance, ion recombination correction model has been suggested by Cavallone et al 2022 for online dosimetry using a Nano Chamber, and Gómez et al 2022 demonstrated the ability to extend the dose rate operating range of an ultra-thin parallel plate ionization chamber by reducing the spacing between electrodes [23,24].…”
Section: Charge-based Dosimetersmentioning
confidence: 99%
“…Several promising modifications to meet the demands of the UHDR beam dosimetry have however recently been investigated for ion chambers and diamond detectors [23][24][25][26]. For instance, ion recombination correction model has been suggested by Cavallone et al 2022 for online dosimetry using a Nano Chamber, and Gómez et al 2022 demonstrated the ability to extend the dose rate operating range of an ultra-thin parallel plate ionization chamber by reducing the spacing between electrodes [23,24]. Furthermore, novel approaches for the feasibility of a diamond detector for UHDR beam dosimetry have also been carried out recently.…”
Section: Charge-based Dosimetersmentioning
confidence: 99%